Differential interaction of hGDH1 and hGDH2 with manganese: Implications for metabolism and toxicity. (September 2015) - Dimovasili, Christina; Aschner, Michael; Plaitakis, Andreas; Zaganas, Ioannis
Highlights: Effect of Mn on human glutamate dehydrogenases (hGDH1 and hGDH2) was studied. Mn exerted a significant inhibitory effect on both hGDH1 and hGDH2. hGDH2 was more sensitive than hGDH1 to Mn, especially under low ADP levels. Mn-induced inhibition was more co-operative for hGDH2 than for hGDH1. These findings might be of pathophysiological relevance for Mn neurotoxicity. Abstract: Manganese (Mn) is an essential trace element that serves as co-factor for many important mammalian enzymes. In humans, the importance of this cation is highlighted by the fact that low levels of Mn cause developmental and metabolic abnormalities and, on the other hand, chronic exposure to excessive amounts of Mn is characterized by neurotoxicity, possibly mediated by perturbation of astrocytic mitochondrial energy metabolism. Here we sought to study the effect of Mn on the two human glutamate dehydrogenases (hGDH1 and hGDH2, respectively), key mitochondrial enzymes involved in numerous cellular processes, including mitochondrial metabolism, glutamate homeostasis and neurotransmission, and cell signaling. Our studies showed that, compared to magnesium (Mg) and calcium (Ca), Mn exerted a significant inhibitory effect on both human isoenzymes with hGDH2 being more sensitive than hGDH1, especially under conditions of low ADP levels. Specifically, in the presence of 0.25 mM ADP, the Mn IC50 was 1.14 ± 0.02 mM and 1.54 ± 0.08 mM for hGDH2 and for hGDH1, respectively (p = 0.0001). Increasing Mn levels potentiated this differential effect, with 3 mM Mn inhibiting hGDH2 by 96.5% and hGDH1 by 70.2%. At 1 mM ADP, the Mn IC50 was 1.84 ± 0.02 mM and 2.04 ± 0.07 mM (p = 0.01) for hGDH2 and hGDH1, respectively, with 3 mM Mn inhibiting hGDH2 by 93.6% and hGDH1 by 70.9%. These results were due to the sigmoidal inhibitory curve of Mn that was more pronounced for hGDH2 than for hGDH1. Indeed, at 0.25 mM, the Hill coefficient value was higher for hGDH2 (3.42 ± 0.20) than for hGDH1 (1.94 ± 0.25; p = 0.0002) indicating that interaction of Mn with hGDH2 was substantially more co-operative than for hGDH1. These findings, showing an enhanced sensitivity of the hGDH2 isoenzyme to Mn, especially at low ADP levels, might be of pathophysiological relevance under conditions of Mn neurotoxicity.